Single-Cell Glia and Neuron Gene Expression in the Central Amygdala in Opioid Withdrawal Suggests Inflammation With Correlated Gut Dysbiosis - O’Sullivan, Sean J.; Malahias, Evangelia; Park, James; Srivastava, Ankita; Reyes, Beverly A. S.; Gorky, Jon; Vadigepalli, Rajanikanth; Van Bockstaele, Elisabeth J.; Schwaber, James S. (Frontiers in Neuroscience, 2019)
Drug-seeking in opioid dependence is due in part to the severe negative emotion associated with the withdrawal syndrome. It is well-established that negative emotional states emerge from activity in the amygdala. More recently, gut microflora have been shown to contribute substantially to such emotions. We measured gene expression in single glia and neurons gathered from the amygdala using laser capture microdissection and simultaneously measured gut microflora in morphine-dependent and withdrawn rats to investigate drivers of negative emotion in opioid withdrawal. We found that neuroinflammatory genes, notably Tnf, were upregulated in the withdrawal condition and that astrocytes, in particular, were highly active. We also observe a decreased Firmicutes to Bacteroides ratio in opioid withdrawal indicating gut dysbiosis. We speculate that these inflammatory and gut microflora changes contribute to the negative emotion experienced in opioid withdrawal that motivates dependence.